Screening of Visually Impaired Children for Health Problems - Dilay Açıl, MSN; Sultan Ayaz, PhD (Elsevier, 2015)
Purpose: Disability is a significant problem and is accepted globally as a health priority in childhood. Like nonvisually impaired children, visually impaired children also need to use health services during childhood. The purpose of this study was to determine the health problems of visually impaired children. Methods: A descriptive design was used. The subjects were 74 children with visual impairment attending primary school (aged 5-14 years), who agreed to participate and whose parents gave permission. Data were collected via physical examination including questionnaires and a physical assessment form. The health screening included physical measurements for height, weight, blood pressure, dental health, hearing, and scoliosis. Results: The mean age of children was 10.43 ± 2.9 years. When the health screening results of children were examined, it was found that 25.7% of the children were overweight or obese, 35.1% of them had dental problems, 27.0% had hearing problems, and 39.2% had scoliosis risk. Systolic and diastolic blood pressures were normal in 91.8% and 93.2% of the children, respectively. Conclusions: These findings showed the important role of school health nurses in performing health screenings directed at visually impaired children who constitute a special group for school health services. Health screening for height, weight, dental health, hearing, and scoliosis is suggested for visually impaired children.